Study of nerve conduction in a population residing at high altitude - Huamaní, Charles (2024)
Objective: To determine the normal values of nerve conduction speed (VCN, acronym in Spanish) parameters from people residing in a city localized at highaltitude. Material and methods: Analytical observational study of people without a comorbid history, residing in Cusco, a city located at 3399 meters above sea level. The motor VCN of the median, ulnar, common peroneal, tibial, and the sensory VCN of the median, ulnar, and sural nerves, their latencies and amplitudes, were evaluated. Results: The study included 56 participants, with a median age of 24 (22-26) years. The latencies of the median, ulnar, and anterior tibial nerves were <5 m/s, and of the peroneal nerves were >5 m/s. The amplitudes of the motor nerves were greater than 5mV and the sensory nerves were above 20μV; the motor velocities were greater than 50m/s, and the sensory nerves were greater than 45m/s. Conclusion: Figures are presented reflecting local VCN reference values, obtained from a young adult population residing in high altitude localities.